Jacques Dupuis faces the inquisition: two essays by Jacques Dupuis on Dominus Iesus and the Roman investigation of his work - Dupuis, Jacques; Burrows, William R. (Pickwick Publ., 2012)
Includes bibliographical references (p. 171-175) and indexes